Employee Performance and the Relationships Between Competence, Motivation, and Work Discipline - Idris, Muhammad; Sultan, Muhammad Salim; Kitta, Syafruddin (JURNAL MANAJEMEN BISNIS, 2021)
The purpose of this study is to explore the effect of competence, work motivation, and work discipline on employee performance at the South Sulawesi Provincial Department of Cooperatives and Small and Medium-Sized Enterprises. This study took a quantitative approach, utilizing procedures such as literature review, observation, interviews, and questionnaires to collect data. This study surveyed 45 individuals using a basic random selection procedure. The data analysis process will include instrument validation (validity and reliability testing), classical assumption testing (normality, multicollinearity, heteroscedasticity, and autocorrelation testing), statistical analysis (multiple regression analysis), and hypothesis testing (test coefficient of determination and partial test). The findings indicated that competence had no discernible effect on the performance of employees at the South Sulawesi Province's Cooperatives and Small and Medium-Sized Enterprises Office. Meanwhile, job motivation and discipline have a substantial impact on employee performance at South Sulawesi Province's Department of Cooperatives and Small and Medium-Sized Enterprises.